2014
DOI: 10.1007/s10741-014-9457-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial oxidative metabolism and uncoupling proteins in the failing heart

Abstract: Despite significant progress in cardiovascular medicine, myocardial ischemia and infarction, progressing eventually to the final end point heart failure (HF), remain the leading cause of morbidity and mortality in the USA. HF is a complex syndrome that results from any structural or functional impairment in ventricular filling or blood ejection. Ultimately, the heart's inability to supply the body's tissues with enough blood may lead to death. Mechanistically, the hallmarks of the failing heart include abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 373 publications
(242 reference statements)
4
72
0
2
Order By: Relevance
“…We found that expression of most genes involved in ROS generation/scavenging did not show significant difference in either of the mutants compared with littermate controls. Differences in gene expression (P < 0.001 compared with littermate controls) were observed only for extracellular superoxide dismutase (Sod 3) (68) and thioredoxin-interacting protein (Txnip) (69) mRNAs in TnT mutants, and uncoupling protein mRNAs (Ucp1, Ucp3) (70) in MyHC mutants (Supplemental Figure 2 and Supplemental Table 2). …”
Section: Basement Membranementioning
confidence: 99%
“…We found that expression of most genes involved in ROS generation/scavenging did not show significant difference in either of the mutants compared with littermate controls. Differences in gene expression (P < 0.001 compared with littermate controls) were observed only for extracellular superoxide dismutase (Sod 3) (68) and thioredoxin-interacting protein (Txnip) (69) mRNAs in TnT mutants, and uncoupling protein mRNAs (Ucp1, Ucp3) (70) in MyHC mutants (Supplemental Figure 2 and Supplemental Table 2). …”
Section: Basement Membranementioning
confidence: 99%
“…In animal model of heart failure induced by pressure overload induced by constriction of the ascending aorta, the expression of UCP2 and UCP3 is downregulated and an increase of ROS generation is enhanced to induce cardiac cell hypertrophy [38, 44]. However this model does not involve FFAs-induced upregulation of UCPs that may protect cell from hypertrophy and dysfunction.…”
Section: General Characteristics Of Ucpsmentioning
confidence: 99%
“…Inappropriate production of oxygen-free radicals in mitochondria, overwhelming the antioxidant defense systems, and the resulting oxidative damage to mitochondrial DNA and mitochondrial proteins have long been recognized as playing a causative role in the development and progression of cardiac remodeling and dysfunction. [16][17][18] However, we cannot exclude that regulation of nicotinamide adenine dinucleotide phosphate oxidase-generated superoxide, as a nonmitochondrial source of ROS, may also be involved in the cardioprotection of PETN against maladaptive remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,[30][31][32] Altered mitochondrial redox balance may decrease the expression of UCP3, whereas mechanical unloading restored UCP3 in the failing human heart. 30,32 Genetic deletion of UCP3 promoted mitochondrial dysfunction and ROS production, leading to adverse cardiac remodeling after MI.…”
Section: Discussionmentioning
confidence: 99%